2016
DOI: 10.1038/srep30776
|View full text |Cite
|
Sign up to set email alerts
|

The environmental carcinogen benzo[a]pyrene induces a Warburg-like metabolic reprogramming dependent on NHE1 and associated with cell survival

Abstract: Cancer cells display alterations in many cellular processes. One core hallmark of cancer is the Warburg effect which is a glycolytic reprogramming that allows cells to survive and proliferate. Although the contributions of environmental contaminants to cancer development are widely accepted, the underlying mechanisms have to be clarified. Benzo[a]pyrene (B[a]P), the prototype of polycyclic aromatic hydrocarbons, exhibits genotoxic and carcinogenic effects, and it is a human carcinogen according to the Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 52 publications
4
74
0
1
Order By: Relevance
“…As B[a]P was reported to trigger a mitochondrial matrix acidification, from approximately 8 to 6.5, in F258 cells 22 , this could explain the appearance of a 24 kDa band presently detected after electrophoresis, thus revealing the presence of active IF1 dimers. Despite the IF1 up-regulation and dimer appearance, only a trend towards decrease for complex V activity was found (decrease by about 12%; data not shown).…”
Section: Discussionmentioning
confidence: 85%
“…As B[a]P was reported to trigger a mitochondrial matrix acidification, from approximately 8 to 6.5, in F258 cells 22 , this could explain the appearance of a 24 kDa band presently detected after electrophoresis, thus revealing the presence of active IF1 dimers. Despite the IF1 up-regulation and dimer appearance, only a trend towards decrease for complex V activity was found (decrease by about 12%; data not shown).…”
Section: Discussionmentioning
confidence: 85%
“…Mitochondria play an important role in oxidative stress upon AhR activation by environmental contaminants, with a AhR-dependent ROS production, a mitochondrial membrane hyperpolarization, a mitochondrial matrix acidification and a decrease in mitochondrial electron transport chain activity in liver cells [29][30][31]. AhR was demonstrated to interact with a subunit of the ATPase synthase M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…We recently showed that B[a]P-induced mitochondrial dysfunction occurs in parallel with a Warburg-like metabolic shift characterized by a reduced cell respiration and an increased lactate production. These changes were associated with alterations in the tricarboxylic acid cycle, which likely involve a reduced activity of the mitochondrial complex II [29].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, interactions with Ah receptor are involved in several of these processes including immunosuppression, modification of proliferative and apoptotic pathways and up‐regulate cellular migration of cancerous cells and epithelial mesenchymal transition . Furthermore, AhR ligands also modulate the endogenous metabolism of glucose, lipids and amino acids . Most importantly, chemicals often act via several mechanisms.…”
mentioning
confidence: 99%